Synthesis and thermal gelation of hydroxypropyl chitin. Issue 50 (4th June 2015) - Li, Chong; Hou, Junxia; Gu, Jianjun; Han, Qiuyan; Guan, Ying; Zhang, Yongjun
<x xml:space="preserve">Abstract</x> Fully water-soluble and thermal gellable hydroxypropyl chitin was synthesized by the modification of chitin with propylene oxide in aqueous NaOH solution, a green and good solvent to chitin.